Some aspects of Mental health care in India - Purohit, Brijesh C. (Utan Kayu Publishing, 2024)
The National Mental Health Policy of India redefines mental health not simply as the absence of mental disorders but as a comprehensive state of well-being. This state enables individuals to realize their own abilities, cope with the normal stresses of life, work productively, and fruitfully contribute to their community. Recent data indicates a troubling increase in both the incidence and severity of mental illnesses globally. This study utilizes a comprehensive dataset provided by the National Institute of Mental Health and Neurosciences (NIMHANS), conducting a detailed factorial analysis to explore the impact of socio-economic factors on mental health across different Indian states and socio-economic strata. Key socio-economic variables such as gender, age, education, and financial dependence were analyzed to determine their influence on mental well-being. Our findings reveal significant relationships where lower levels of education and higher levels of financial dependence correlate with poorer mental health outcomes. These insights highlight the necessity for tailored mental health strategies that address specific local and socio-economic contexts rather than applying a uniform approach across diverse populations. This research underscores the importance of situational and context-aware health policies and interventions that can effectively address and mitigate the unique challenges faced by various groups within the population. The implications of these findings support the call for a more nuanced and strategic approach to mental health policy-making that can better serve India’s diverse societal needs.